1996
DOI: 10.1021/jp961214z
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopic Studies of Carbon Clusters Trapped in Solid Parahydrogen

Abstract: Small carbon clusters produced by laser ablation of a carbon rod are trapped in solid parahydrogen at 4.8 K. Infrared spectra show the presence of C3, C5, C9, and a few new clusters. The observed vibrational spectra with multiplet structures are tentatively associated with hindered rotation of the clusters. Temperature dependence of the IR spectra reveals the diffusion of C3 and C5 clusters in the crystal at around 8 K, while no diffusion of C9 and the larger clusters is noticed. Any hydrocarbons which might b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…We recently reviewed the literature on MIS of trapped atomic impurities in SMH [3], as part of our work on condensed phase reactions of energetic species. We have begun to employ spectroscopic characterization of molecular impurities in SMH, a field showing considerable current activity [4][5][6][7][8][9][10][11][12]. However, certain difficulties in using the SMH as matrix hosts remain to be overcome.…”
Section: Pacs Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reviewed the literature on MIS of trapped atomic impurities in SMH [3], as part of our work on condensed phase reactions of energetic species. We have begun to employ spectroscopic characterization of molecular impurities in SMH, a field showing considerable current activity [4][5][6][7][8][9][10][11][12]. However, certain difficulties in using the SMH as matrix hosts remain to be overcome.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Several advantages of using solid parahydrogen (pH 2 [13]) as a matrix host have been extolled by collaborating groups in Kyoto and Chicago [4,7,8,11,12]. They note the spherical nature of J=0 pH 2 , which is preserved in SMH [1].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…[1][2][3][4][5] We have been exploiting this matrix to develop high-resolution matrix isolation spectroscopy. [3][4][5][6][7][8][9] So far, we have shown that several monomeric molecules trapped in solid parahydrogen give much sharper infrared absorption spectra than those observed in the conventional matrices. This is attributable to the extreme inertness of the matrix which makes the homogeneous spectral linewidth very narrow and the quantum nature of the solid hydrogen which suppresses the inhomogeneous linewidth caused by multiple trapping sites often formed in the conventional rare gas matrices.…”
Section: Introductionmentioning
confidence: 97%
“…Solid para-hydrogen as a host for atomic impurities has been the subject of many recent theoretical [1][2][3][4][5] and experimental studies, [6][7][8][9] in part because such systems might play a role in the development of future cryo-propellants. 10 Experiments have shown that atomic impurities, such as Li, B, and Al, can be metastably trapped in a solid hydrogen matrix.…”
Section: Introductionmentioning
confidence: 99%